Desenvolvimento de espumas a base de amido de mandioca - Stoffel, Fernanda (My University, 2015)
The environmental impact caused by improper disposal of packaging materials based on synthetic polymers, arouses interest in development packaging from biodegradable materials. The objective of this study was to develop and characterize trays base of cassava starch foam for food packaging, obtained by the thermal expansion process. Different proportions of starch and water, as blowing agent, in the formulation of the starch foams was tested. As plasticizers were used glycerol, sorbitol, and poly (vinyl alcohol) (PVA) at concentrations of 2.5; 5.0 and 7.5% w/w on starch weight. In order to improve the hydrophilic characteristics of the foams, coating was applied of poly (lactic acid) (PLA) in the surface of the trays. The application of the trays as packaging strawberries in storage was tested. Packaging characterization was performed by thickness and density analysis, SEM, water absorption capacity (WAC), solubility, sorption isotherms, tensile strength, angle of contact and enzymatic degradation. The ratio starch:water who produced foams with the best combination of density, water absorption capacity and visual aspect characteristics was 47.5:52.5. The starch additive resulted in foams with the highest possibility of application as packaging for food for presenting the lowest WAC be less soluble and lowest values equilibrium moisture, was PVA concentration of 5%. The use of PLA-based coating on the surface of the starch foam trays resulted in a decrease of 86% in WAC trays and contact angle of 84.4 ° (higher hydrophobicity). The models that best fit the sorption isotherm of uncoated trays are the GAB and Oswin models. While for trays with PLA coating, Oswin model presents the best fit. The assay of enzymatic degradation by microbial amylases revealed the occurrence of the hydrolysis of starch in the first 8 hours of the test, indicating the biodegradability characteristics of the trays. The results of this study, obtained through the applicability of the test trays prove the possibility of the use of tapioca starch-based packing covered with PLA foods with high water activity.
O impacto ambiental causado pelo descarte indevido de embalagens a base de polímeros sintéticos, desperta interesse na necessidade de desenvolvimento de embalagens a partir de materiais biodegradáveis. O objetivo deste trabalho foi desenvolver e caracterizar bandejas a base de espuma de amido de mandioca para embalagem de alimentos, obtidas pelo processo de expansão térmica. Foram testadas diferentes proporções de amido e água, como agente expansor, na formulação das espumas de amido. Como plastificantes, foram utilizados o glicerol, sorbitol e poli (álcool vinílico) (PVA), nas concentrações de 2,5; 5,0 e 7,5% m/m sob a massa de amido. A fim de melhorar as características de hidrofilia das espumas, foi aplicado revestimento a base de poli (ácido lático) (PLA) na superfície das bandejas. Testou-se a aplicação das bandejas como embalagem no armazenamento de morangos. A caracterização das embalagens foi realizada através de análises de espessura e densidade, MEV, capacidade de absorção de água (CAA), solubilidade, isotermas de sorção, resistência à tração, ângulo de contato e degradação enzimática. A proporção amido:água que produziu espumas com a melhor combinação entre as características de densidade, capacidade de absorção de água e aspecto visual foi 47,5:52,5. O aditivo que resultou em espumas de amido com a maior possibilidade de aplicação como embalagem para alimentos, por apresentar a menor CAA, ser menos solúvel e com os valores mais baixos de umidade de equilíbrio, foi o PVA em concentração de 5%. A aplicação de revestimento a base de PLA na superfície das bandejas de espuma de amido resultou em diminuição de 86% na CAA das bandejas e ângulo de contato de 84,4° (maior hidrofobia). Os modelos que melhor se ajustam a isoterma de sorção das bandejas sem revestimento são os de GAB e Oswin. Enquanto que para bandejas com revestimento de PLA, o modelo de Oswin apresenta o melhor ajuste. O ensaio de degradação enzimática por amilases microbianas revelou ocorrência da hidrólise do amido nas primeiras 8 horas do teste, indicando característica de biodegradabilidade das bandejas. Os resultados do presente estudo, obtidos através do teste de aplicabilidade das bandejas, comprovam a possibilidade da utilização da embalagem à base de amido de mandioca revestidas com PLA em alimentos com alta atividade de água.
Keywords: Embalagens; Mandioca; Mandioca - Processamento; Expansão (Calor); Packaging; Cassava; Cassava - Processing; Expansion (Heat)